Support Needs of Patients with Cushing’s Disease and Cushing’s Syndrome: Results of a Survey Conducted in Germany and the USA - Ilonka Kreitschmann-Andermahr; Sonja Siegel; Christa Gammel; Karen Campbell; Leslie Edwin; Agnieszka Grzywotz; Victoria Kuhna; Maria Koltowska-Häggström; Oliver Müller; Michael Buchfelder; Bernadette Kleist (International Journal of Endocrinology)
Background. Cushing’s disease (CD) and Cushing’s syndrome (CS) are chronic illnesses, characterized by symptoms of prolonged hypercortisolism, which often changes to hypocortisolism after successful treatment. In view of the high disease burden of CD/CS patients and long-term impaired quality of life, the present survey was conducted to gain information about subjective illness distress and patients’ specific needs in terms of supportive measures beyond medical interventions. Patients and Methods. Cross-sectional questionnaire study including patients with CD treated in 2 German neurosurgical tertiary referral centers and CD/CS patient members of a US-based patient support group completed a survey inquiring about disease burden, coping strategies, and support needs. Additionally, the degree of interest in different offers, e.g., internet-based programs and seminars, was assessed. Results. 84 US and 71 German patients answered the questionnaire. Patients in both countries indicated to suffer from Cushing-related symptoms, reduced performance, and psychological problems. 48.8% US patients and 44.4% German patients stated that good medical care and competent doctors helped them the most in coping with the illness. US patients were more interested in support groups (p=0.035) and in courses on illness coping (p=0.008) than the German patients, who stated to prefer brochures (p=0.001). 89.3% of US patients would attend internet-based programs compared to 75.4% of German patients (p=0.040). There were no differences between groups for the preferred duration of and the willingness to pay for such a program, but US patients would travel longer distances to attend a support meeting (p=0.027). Conclusion. Patients in both countries need skilled physicians and long-term medical care in dealing with the effects of CD/CS, whereas other support needs differ between patients of both countries. The latter implies that not only disease-specific but also culture-specific training programs would need to be considered to satisfy the needs of patients in different countries.